2017
DOI: 10.1016/j.neuron.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Neural Manifolds for the Control of Movement

Abstract: The analysis of neural dynamics in several brain cortices has consistently uncovered low-dimensional manifolds that capture a significant fraction of neural variability. These neural manifolds are spanned by specific patterns of correlated neural activity, the “neural modes.” We discuss a model for neural control of movement in which the timedependent activation of these neural modes is the generator of motor behavior. This manifold-based view of motor cortex may lead to a better understanding of how the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
573
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(597 citation statements)
references
References 68 publications
20
573
4
Order By: Relevance
“…Our work is also of potential relevance to study another timely issue in neuroscience, that is the relevance for perception of the information about sensory variables carried by neural activity [19,45]. This is a crucial issue to resolve the diatribe about the nature of the neural code, that is the set of symbols used by neurons to encode information and produce brain function [46][47][48]. Addressing this problem requires mapping the information in the multivariate distribution of variables such as the stimuli presented to the subject, the neural activity elicited by the presentation of such stimuli, and the behavioral reports of the subject's perception.…”
Section: Potential Implications For Systems Biology and Systems Neuromentioning
confidence: 91%
“…Our work is also of potential relevance to study another timely issue in neuroscience, that is the relevance for perception of the information about sensory variables carried by neural activity [19,45]. This is a crucial issue to resolve the diatribe about the nature of the neural code, that is the set of symbols used by neurons to encode information and produce brain function [46][47][48]. Addressing this problem requires mapping the information in the multivariate distribution of variables such as the stimuli presented to the subject, the neural activity elicited by the presentation of such stimuli, and the behavioral reports of the subject's perception.…”
Section: Potential Implications For Systems Biology and Systems Neuromentioning
confidence: 91%
“…To this purpose we exploited the concept of neural manifolds (Gallego et al, 2017) finding a holding subspace where neuronal trajectories of the correct-stop trials, as well in the initial part of no-stop and wrong-stop trials, are confined. The escape of neuronal trajectories from this subspace determines the transition from the prepare-and-hold to the movement generation.…”
Section: Movement Control In a State-space Frameworkmentioning
confidence: 99%
“…Our analysis of neural data is based on conceptualizing the collective activity of neurons as a point in a high-dimensional neural state space, where each coordinate is the activity level of one neuron. It has been observed that in many scenarios, the neural state seemed confined to a lower-dimensional region of the neural state space, termed the "neural manifold" [14][15][16][17][18][19][20][21][22][23][24][25] . We analyzed the geometrical structure of the neural manifold by examining two types of state-space directions, defined by the neural encoding and decoding of the above-mentioned task variables as explained below.…”
Section: Introductionmentioning
confidence: 99%